1998
DOI: 10.1038/sj.sc.3100482
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculatory stimulation, quality of semen and reproductive aspects in spinal cord injured men

Abstract: This is a retrospective study of 39 male spinal cord injured patients who, over the last 5 years, have consulted us for ejaculatory dysfunction or infertility. All of these patients underwent at least two distinct sessions during which attempts were made to induce an ejaculation by vibratory stimulation, electric stimulation, or by using subcutaneous physostigmine. A semen analysis was performed each time that an ejaculate was obtained. By one or more of these techniques, 75% of these subjects were able to eja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
0
12
1
3
Order By: Relevance
“…This in later combined by intracytoplasmic sperm injection (ICSI) procedure [11,12] became the only and best method, which is available for all patients by neurological-psychogenic or physiologic an ejaculation [13,14,16]. It was an evolution in infertility treatment [13,14,20]. In this study, the electro ejaculation followed by ICSI procedure was one of the four methods for infertility treatment of an ejaculatory and impotence man.…”
Section: Discussionmentioning
confidence: 93%
“…This in later combined by intracytoplasmic sperm injection (ICSI) procedure [11,12] became the only and best method, which is available for all patients by neurological-psychogenic or physiologic an ejaculation [13,14,16]. It was an evolution in infertility treatment [13,14,20]. In this study, the electro ejaculation followed by ICSI procedure was one of the four methods for infertility treatment of an ejaculatory and impotence man.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, as others suggested [7,16], midodrine might be a functional treatment for anejaculation in men with SCI because it has a rapid onset of action (within 10-30 min), because it reaches its maximum effect within 1 h, can last 3-4 h, and because it is easy to use and well tolerated by patients. Furthermore, while midodrine targets specific α -adrenergic receptors rather than the overall autonomic system, its limited side-effects might be grounded on neurophysiological substrates that contrast with the massive effects reported with anticholinesterase drugs [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies used cholinesterase inhibitors such as intrathecal prostigmine (neostigmine) [12,13] and s.c. injections with physostigmine [14,15], and found them to be effective for triggering ejaculation in these men. However, because these cholinergic drugs have powerful sideeffects, including severe headaches, nausea, vomiting, abdominal cramps, diarrhoea (and even one reported death from cerebral haemorrhage) they were abandoned as a treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…However, when adding the number of sperm isolated from the urine (retrograde fraction) after both procedures, only a slight advantage in the sperm quality from PVS was seen. Two other recent studies 23,41 demonstrated that the motility rate was signi®cantly better in total ejaculates (antegrade+retrograde ejaculations) from PVS compared to EEJ. Whether the dierence in sperm motility and viability between PVS and EEJ may have any in¯uence on the reproduction capability will have to be evaluated in a randomized prospective study including SCI men and their partners undergoing fertility treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The number of sperm with low motility exhibited by this patient is in accordance with the literature. According to Le Chapelain et al 23 the mean semen volume procured by PVS is greater than that obtained using EEJ and the percentage of motile sperm was signi®cantly lower in semen procured by EEJ as opposed to that collected by PVS. In the present case we would not try vibratory ejaculation plus vaginal injection of the semen because the success rate of this method is very low and the patient's partner is not so young, demanding a quick solution.…”
Section: Comments By Dr Rocha and Dr Barrosmentioning
confidence: 99%